A high‐resolution 3D atlas of the spectrum of tuberculous and COVID‐19 lung lesions. Issue 11 (26th October 2022) - Wells, Gordon; Glasgow, Joel N; Nargan, Kievershen; Lumamba, Kapongo; Madansein, Rajhmun; Maharaj, Kameel; Perumal, Leon Y; Matthew, Malcolm; Hunter, Robert L; Pacl, Hayden; Peabody Lever, Jacelyn E; Stanford, Denise D; et al.
Abstract: Our current understanding of the spectrum of TB and COVID‐19 lesions in the human lung is limited by a reliance on low‐resolution imaging platforms that cannot provide accurate 3D representations of lesion types within the context of the whole lung. To characterize TB and COVID‐19 lesions in 3D, we applied micro/nanocomputed tomography to surgically resected, postmortem, and paraffin‐embedded human lung tissue. We define a spectrum of TB pathologies, including cavitary lesions, calcium deposits outside and inside necrotic granulomas and mycetomas, and vascular rearrangement. We identified an unusual spatial arrangement of vasculature within an entire COVID‐19 lobe, and 3D segmentation of blood vessels revealed microangiopathy associated with hemorrhage. Notably, segmentation of pathological anomalies reveals hidden pathological structures that might otherwise be disregarded, demonstrating a powerful method to visualize pathologies in 3D in TB lung tissue and whole COVID‐19 lobes. These findings provide unexpected new insight into the spatial organization of the spectrum of TB and COVID‐19 lesions within the framework of the entire lung. Synopsis: 3D X‐ray microscopy (micro‐Computed Tomography) was used to establish an initial atlas of TB and COVID‐19 lung lesion types in the human lung. Previously hidden features within polymorphic TB lesions were reconstructed in 3D, which revealed a complex branched morphology reminiscent of airways. Varying degrees of calcification could be readily observed within necrotic TB lesions and mycetomas. Loss of central vasculature and abnormalities in peripheral vasculature were observed in COVID‐19 lungs. 3D μCT imaging was successfully applied to formalin‐fixed and paraffin‐embedded tissue. Thus, this technique could be applied to established libraries of human tissue. Abstract : 3D X‐ray microscopy (micro‐Computed Tomography) was used to establish an initial atlas of TB and COVID‐19 lung lesion types in the human lung.